Literary translation : a practical guide - Landers, Clifford E. (Topics in translation, 2001)
"In Literary Translation: A Practical Guide, both beginning and experienced translators will find pragmatic techniques for dealing with problems of literary translation, irrespective of the original language. Certain challenges and certain themes recur in translation, whatever the language pair. This guide proposes to help the translator navigate through them. There are guidelines that can help us work our way through, to use a Borgesian metaphor, the seemingly infinite labyrinth of forking paths. That is the purpose of this book."--Jacket